Effects of workplace spirituality on employee performance mediated by personal values and job commitment - Osman-Gani, Aahad M.; Anwar, Md. Aftab (2014)
Workplace spirituality has recently become an important area of research for studying individual performance enhancement, particularly after recent episodes of corporate scandals and ethical violence in the workplace. Although some research has been done on spirituality and workplace performance, almost no empirical study were found to have investigated the effects of personal values and job commitment in the relationships among spirituality and performance. Particularly, no empirical study was done in the Asian context. This paper presents the findings of an empirical investigation conducted in Malaysia on the direct and mediation effects of workplace spirituality on employee performance. The results show significant positive effects of spirituality on employee performance. The findings also revealed the significant mediation effects of personal values and commitment to job due to higher levels of spirituality. These findings have important implications for HRD research and practice. The paper concludes by mentioning some of these implications for HRD scholars and practitioners.